AN EXTENSIONIST STUDENT LOOK AT THE PROJECT GUIDANCE FOR FAMILIES OF CHILDREN WITH SPECIAL EDUCATIONAL NEEDS - Filipe-Kembo, João (Revista Gênero e Interdisciplinaridade, 2023)
This article aims to report, on the one hand, the experiences lived at the Escola Superior Pedagógica do Bengo as a degree student in the Education Sciences course, Psychology Teaching option, within the scope of university university extension actions in the community of Caxito with the families of children with special educational needs through the university extension project “Guidance to Families of Children with Special Educational Needs”, and on the other hand, the experiences lived and acquired, from 2017 to 2021, as an employee of the same institution while technician at the Executive Secretariat of the Observatory for Education and Social Development – ​​OBEDS, the body responsible for project management and all scientific research and university extension activities. This time, it is intended to demonstrate the importance of university graduation in student training, its contribution in solving social problems, its role and importance in the management of higher education institutions.